Retraining and Nutritional Strategy of an Endurance Master Athlete Following Hip Arthroplasty: A Case Study - Louis, Julien; Tiollier, Eve; Lamb, Antonia; Bontemps, Bastien; Areta, Jose; Bernard, Thierry (Frontiers in Sports and Active Living, 2020)
Retraining and resuming competition following surgery is challenging for athletes due to the prolonged period of reduced physical activity and subsequent alteration in body composition and physical performance. This is even more challenging for master athletes who endure the additional effect of aging. Within this context, the purpose of this study was to evaluate the feasibility and benefits that evidence-based nutritional and training recommendations could have on the time course of reconditioning and retraining following hip arthroplasty in an endurance master triathlete. During 38 weeks (from 6 weeks prior to surgery through to the return to competition in week 32), the athlete was provided with detailed training and nutritional recommendations. Dietary intake (via the remote food photographic method), body composition (via DXA), peak oxygen uptake (VO2peak), peak power output (PPO), cycling efficiency (GE) and energy availability (EA) were assessed 6 weeks pre- and 8, 12, 18, 21 and 25-weeks post-surgery. Training load was quantified (via TRIMP score and energy expenditure) daily during the retraining. Total body mass increased by 8.2 kg (attributable to a 3.5 and 4.6 kg increase in fat mass and lean mass, respectively) between week -6 and week 8 despite a reduction in carbohydrate (CHO) intake post-surgery (<3.0g/kg body mass/day). This was accompanied with a decrease in VO2peak, PPO, and GE due to a drop in training load. From week 7, the athlete resumed training and was advised to increase gradually CHO intake according to the demands of training. Eventually the athlete was able to return to competition in week 32 with a higher PPO, improved VO2peak and GE. Throughout retraining, EA was maintained around 30 kcal/kg Lean Body Mass/day, protein intake was high (~2g/kg/day) while CHO intake was periodized. Such dietary conditions allowed the athlete to maintain and even increase lean mass, which represents a major challenge with aging. Data reported in this study show, for the first time, the conditions required to recover and return to endurance competition following hip surgery.